A study on the mechanism and control technology of strong mine pressure in parallel coal pillar and hard roof mining - Zhou, Haifeng; Huang, Qingxiang; He, Yanpeng; Wang, Qingxiong; Wei, Yehao (Frontiers in Earth Science, 2024)
In multi-seam mining, as mining ranges expand and depths increase, the strong ground pressure exerted on lower coal seam working faces (WFs) or roadways by coal pillars (CPs) and hard roof between interburden becomes increasingly severe, leading to periodic roof fall accidents. This study focused on the 42108 WF of the 4-2 coal seam in Buertai Coal Mine of Shendong Mining. It combined field tests, theoretical research, and numerical calculations to investigate the superposition or amplification of ground pressure as the WF traversed the CP with the hard roof between interburden. Ground pressure behavior of the WF entering and exiting the CP stage progressed from strong to weak: exiting the CP > under the CP > entering the CP, with strong ground pressure being prone to occur during the CP stage. We proposed the influence mechanism of strong ground pressure and a seesaw structural mechanics model under mining conditions with parallel CPs and hard roofs. The relationship between geometric structure movement and stress evolution of the seesaw space of the overlying hard roof was analyzed, revealing the mechanism behind stress increase, evident damage, and the likelihood of dynamic disasters within 5-10 m from the CP boundary of the WF. The SCF of advance abutment pressure in the coal wall was the primary controlling factor determining seesaw instability, effectively ensuring safe and efficient mining practices. This research holds significant theoretical importance and practical engineering value for controlling strong mine pressure under overlying CPs and hard roofs.